45 Increased Lysine: ME ratio improves grower pig performance during a PRRSV challenge. (10th April 2018) - Schweer, W P; Mendoza, O F; Shull, C M; Lehman, J; Gaines, A M; Schwartz, K J; Gabler, N K
Abstract: Porcine reproductive and respiratory virus (PRRSV) significantly reduces pig performance. The AA requirements and Lys:ME of health challenged pigs for optimum performance are poorly understood. Two experiments were conducted to evaluate the effect of increasing SID Lys:ME (g Lys per Mcal ME) on growth performance during a PRRSV challenge. In Exp. 1, 379 barrows (51.3 ± 0.3 kg BW) were allotted to one of six diets (1.87-3.41 Lys:ME) for a 35-d growth study. In Exp. 2, 389 barrows (29.2 ± 0.23 kg BW) were allotted to one of six diets (2.39-3.91 Lys:ME) for a 49-d growth study. These isocaloric diets represented 80, 90, 100, 110, 120 and 130% of NRC SID Lys requirement. For each Exp., pigs were randomly allocated to two barns of 24 pens each with 7-9 pigs/pen (4 pens/diet/health status). On day 0, one barn was inoculated with live PRRSV, one barn sham inoculated (control), and all pigs were started on experimental diets. Pen growth performance and feed intake were recorded weekly and G:F calculated. Breakpoint analysis was used to determine the Lys:ME ratio that maximized ADG and G:F over the 35 or 49-d test periods for Exp. 1 and 2, respectively. In Exp. 1 increasing Lys:ME increased ADG (linear P =0.07, quadratic P =0.02) and G:F (linear P =0.09, quadratic P =0.02) in control pigs over 35-d. In PRRSV pigs, ADG and G:F increased linearly with increasing Lys:ME ( P =0.001). The Lys:ME for optimum ADG and G:F during PRRSV challenge was 3.05 and 3.15, respectively, compared to 2.24 and 2.51, respectively, in control pigs using a one-slope broken-line model. In Exp. 2 control pigs became naturally infected after 21 dpi. Prior to infection, ADG and G:F increased with increasing Lys:ME in control pigs (linear P <0.001, quadratic P <0.05). The response was similar in PRRSV pigs ( P <0.01, linear and quadratic). Over the 49-d period, increasing Lys:ME improved ADG (linear P <0.001) and G:F (linear P <0.001, quadratic P =0.02) in naturally infected pigs. The response was similar in experimental infection for ADG (linear P <0.001, quadratic P =0.04) and G:F (linear P =0.009). The optimum ratio for ADG was 2.90 and 3.16 for natural and experimental infection, respectively, using a one-slope broken-line model. Using a 2-slope broken-line model, a 3.12 and 3.17 Lys:ME maximized G:F for natural and experimental infection, respectively. In summary, increasing Lys:ME ratio by 110 to 120% improved performance and feed efficiency during a PRRSV challenge. This response was similar in experimental and natural PRRSV infections.